Pseudohomozygous dysfibrinogenemia. Issue 6 (21st August 2021) - Peck, Rachel C.; Fitzgibbon, Lucy; Reilly‐Stitt, Christopher; Doherty, Christopher; Phillips, Emma; Mumford, Andrew D.
Abstract: Hypodysfibrinogenemia (HD) is a heterogeneous disorder in which plasma fibrinogen antigen and function are both reduced but discordant. This report addresses the key clinical question of whether genetic analysis enables clinically useful subclassification of patients with HD. We report a new case and identify a further eight previously documented cases that have the laboratory features of HD but biallelic inheritance of quantitative and qualitative fibrinogen gene variants. The cases displayed both bleeding and thrombosis and sometimes had undetectable fibrinogen activity. In all cases, the predicted effect of the coinherited variants is reduced levels of circulating fibrinogen that is all dysfunctional. We propose the term pseudohomozygous dysfibrinogenemia for this subtype of recessively inherited HD that is distinct from the more commonly recognized monoallelic HD caused by a single fibrinogen gene variant.